Contribuições de Espinosa para o conceito de saúde mental - Lima, Orion Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This study aims to understand the extent to which Spinoza's contributions are important to the concept of mental health. Historically, mental illness was outlined as shadows of symptoms experienced by individuals, so that madness became synonymous with error, ie, everything that constitutes misrepresentation of reality. From this perspective, the madman became an alienated alien to himself and the world, in short, a non-subject. Understood in this sense, mental illness takes on the character of biological imbalance, specifically speaking on the brain sphere. As a synonym for error, the patient should, isolated from the world, look for a fit with reality. In this universe of isolation madness makes the individual the subject of unreason, in other words, the subject, is no longer the protagonist of his own story. In this conception of institutionalization of madness, mental illness is molded from the concept of disorder or misfit that reveals it self in a bizarre symptoms. There is no concern for the individual, understood here in its entirety. With the advent of so-called psychiatric reform, trumpeted by the ideas of Basaglia, Rotelli and stimulated primarily by a philosophy of emancipation of the subject proposed by Foucault begins to promote the deconstruction of a psychiatric facility founded on the notion of power-knowledge . The very establishment of mental illness suggests that a subjectivity different thinking is emerging, so it makes no sense to treat the symptoms aside from the subject as well as their existence and their suffering. For a long time we focused our attention on the concept of mental illnesses and consequently their symptoms. We build our theories an...(Complete abstract click eletronic access below)
Keywords: Saude mental - Reabilitação; Filosofia; Loucura; Spinoza, Benedictus de 1632-1677; Philosophy